Autoantibody profiles associated with morbidity and mortality in scleroderma renal crisis. (25th January 2022) - Tsuji, Hideaki; Kuramoto, Nobuo; Sasai, Tsuneo; Shirakashi, Mirei; Onizawa, Hideo; Kitagori, Koji; Akizuki, Shuji; Nakashima, Ran; Watanabe, Ryu; Onishi, Akira; Murakami, Kosaku; Yoshifuji, Hajime; et al.
Abstract: Objective: The aim of this study was to investigate association of autoantibodies with scleroderma renal crisis (SRC) among Japanese patients. Methods: The clinical characteristics and mortality of 330 patients with sytemic screlosis (SSc) at Kyoto University Hospital were retrospectively analysed, focusing on possible association with anti-topoisomerase I (anti-topo I), anti-centromere (ACA), anti-RNA polymerase III (RNAPIII) and/or anti-U1-RNP. Logistic regression analyses were performed to reveal any association of these autoantibodies with the development and mortality of SRC. Results: SRC was observed in 24 out of 330 SSc patients, including patients with anti-topo I ( n  = 12/24, 50%), anti-RNAPIII ( n  = 7/24, 29%), anti-U1-RNP ( n  = 5/24, 21%) and ACA ( n  = 3/24, 13%). Anti-U1-RNP [odds ratio (95% CI), 3.63 (1.11, 10.2)], anti-topo I [3.22 (1.37, 7.57)] and anti-RNAPIII (3.29 [1.16, 8.70]) were associated with the development of SRC. Furthermore, anti-topo I [6.00 (1.11, 41.1)] was associated with 1-year mortality of SRC. The 1-year survival rate after the onset of SRC among all patients and among those positive for anti-topo I was 54% and 33%, respectively. In contrast, the survival rate in patients negative for anti-topo I was 75%, of which the survival rate of patients positive for anti-RNAPIII and ACA was 83% and 100%, respectively. Conclusion: Specific SSc-related autoantibodies were associated with the morbidity and mortality of SRC.